Characterization of Graphene Oxide Coatings onto Optical Fibers for Sensing Applications. (2015) - Alberto, Nélia; Vigário, César; Duarte, Daniel; Almeida, Nuno A.F.; Gonçalves, Gil; Pinto, João L.; Marques, Paula A.A.P.; Nogueira, Rogério; Neto, Victor
Abstract: Results of the preparation and characterization of graphene oxide–optical fiber coatings will be presented, considering its potential use for sensing applications. The coatings were deposited using the electrostatic self–assembly method, considering different parameters (average sheet size of the graphene oxide colloidal solutions, the number of the deposited layers and the coating methodology) and characterized through SEM and Raman analyses. Aiming to explore this scheme for sensing applications, graphene oxide-coated tilted fiber Bragg gratings were characterized to refractive index variations. An improvement on the sensitivity was obtained and this result suggests that this could be a promising research field for the development of a new line of sensors.